Production of biopolymers from watermelon mesocarp: structural characterization, cytogenotoxicological safety, and antioxidant activity - da Silva, Juliana Gonella Fornielles; Cerqueira, Igor Henrique; Paris Junior, José Alberto; da Silva, Lucas Henrique Domingos; Colturato, Vitória Maria Medalha; de Abreu Fernandes, Paula; Oliveira, Thaís Lourenço; Dametto, Alessandra Cristina; Dias, Diógenes dos Santos [UNESP]; Ribeiro, Clovis Augusto [UNESP]; de Oliveira, Luiz Fernando Cappa; da Silva Barud, Hernane; et al. (Springer Nature, 2025)
This study aimed to produce flexible and optically semi-transparent biopolymers exclusively from watermelon mesocarp. Washed (WM-W) and non-washed (WM-NW) films were obtained hydrothermally, followed by grinding and casting steps, and characterized, targeting correlations among chemical structure, film-forming protocol, cytogenotoxicological safety, and antioxidant activity. The morphological aspects were analyzed using scanning electron microscopy and, according to thermogravimetry measurements, the films are thermally stable with glass transition temperatures determined with differential scanning calorimetry ranging from 12.1 to 77.6 °C for WM-NW and 56.0 °C for WM-W. These differences are probably due to the presence of soluble carbohydrates. The elastic modulus and tensile strength ranged from 88 MPa to 1.1 GPa and from 0.4 MPa to 3.4 MPa, respectively, while the elongation at break decreased from 0.7 to 0.46%. The chemical groups were identified using FTIR and FT-Raman spectroscopy while the crystallinity index (from 10.4 to 50%) was determined with X-ray diffraction. Additionally, the relative water absorption, swelling ratio, water barrier properties, and fluid handling capacity were assessed. WM-NW showed slightly higher cytotoxicity than the WM-W film in cultures of human keratinocytes (HaCat cells). Furthermore, both exhibited antioxidant potential and lacked mutagenic effects, supporting their safe use in diverse value-added applications, particularly in medical devices.
Keywords: Antioxidant activity; Cytotoxicity; Eco-friendly materials; Flexible fims; Mutagenicity; Watermelon mesocarp